The economic role of mass hiring - Rodríguez Chávez, Reyler Yulfo (2011)
This article addresses the issue of mass contracts from a perspective of law and economics, with the aim of providing guidelines on the economic function of this form of contracts within the present context of economic exchanges, characterized by the presence of two distinct factors, mass society and the mass production of goods and services. Among these, it is mass contracting, in its different forms, such as the standard form contract (contract of adhesion) and the general contracting articles that allow the articulation of trade operations thereby consolidating legal bonds between the businessmen in charge of supplying goods and services and the consumers who demand them. At the same time, mass contracting not only provides legal security to those mass contracting relations but also makes them efficient and effective according to the market requirements. Thus, this form of contracting is not solely an «objective/means» that links both poles (businessmen and consumers) but also enables the reduction of transactional costs in time, money and effort, thereby constituting a means to an end.